KAJIAN PELAKSANAAN PENDIDIKAN KARAKTER DI SDN SUNGAI JINGAH 6 BANJARMASIN - Reja Fahlevi; Raihanah Sari; Fathul Jannah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This study aims to determine student behavior and the obstacles found in the implementation of character education at SDN Sungai Jingah 6 Banjarmasin, as well as the solutions taken. The approach in this study uses a quantitative descriptive approach with a survey method. The sampling technique used purposive sampling, namely by taking a sample of all teachers consisting of 11 people and also students of class V with a total of 20 students as respondents. The research instruments used were interviews, questionnaires, and observations. The results of the research show that the behavior of students in applying character education which includes religious character, honesty, diligence, discipline, and care / responsibility is categorized as quite good. As for the problem of the lack of cooperation from parents to further foster students when they are at home, as well as their daily social environment. So the solution 3to these problems is to make regular visits to students' homes by the homeroom teacher.Â